A metallocene catalyst, its preparation method and application
Patent Information
- Application Number
- CN202611064690.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-08-14
AI Technical Summary
然而,溶液聚合存在以下缺陷:需要消耗大量有机溶剂,溶剂回收、精制、循环利用系统投资和运行能耗极高;高温条件导致茂金属催化剂热稳定性面临严峻考验,链转移反应限制了超高分子量产品的制备;大量溶剂使用带来挥发性有机物排放等环保压力
(1)活性寿命显著延长:在80℃气相聚合条件下,本发明催化剂的活性半衰期达6小时,较常规MAO/硅胶负载催化剂(活性半衰期约30~60分钟)延长6~12倍。
Smart Images

Figure CN122562993A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyolefin catalyst technology, specifically to a metallocene catalyst, its preparation method, and its application. Background Technology
[0002] Polyolefin elastomers (POEs) are a class of thermoplastic elastomers copolymerized from ethylene and α-olefins (such as 1-butene, 1-hexene, and 1-octene) through coordination polymerization. Their molecular chains contain both crystallizable polyethylene segments and amorphous regions introduced by α-olefins, endowing the materials with excellent mechanical properties, aging resistance, and processing rheology. Since the 1990s, when Dow Chemical in the United States achieved industrial-scale production of POE using a defined geometry metallocene catalyst (CGC) combined with the Insite™ solution polymerization process, POEs have been widely used in high-end fields such as automotive lightweighting, photovoltaic encapsulation films, wires and cables, shoe material foaming, and plastic modification.
[0003] Currently, the mainstream technology for global POE industrial production is solution polymerization. Solution polymerization is carried out in high-temperature (120~180℃) hydrocarbon solvents, resulting in a uniform distribution of catalyst active sites, easy control of reaction heat and mass transfer, and precise control of product molecular structure. However, solution polymerization has the following drawbacks: it requires large amounts of organic solvents, leading to extremely high investment and energy consumption for solvent recovery, purification, and recycling systems; the high-temperature conditions severely test the thermal stability of metallocene catalysts, and chain transfer reactions limit the preparation of ultra-high molecular weight products; and the large-scale use of solvents brings environmental pressures such as volatile organic compound emissions.
[0004] Compared to solution polymerization, gas-phase polymerization requires no inert solvents or liquid monomers as a reaction medium. It features a shorter process flow, lower equipment investment, lower energy consumption, and is more environmentally friendly, making it widely used in polyethylene and polypropylene production. Applying gas-phase polymerization to POE production is expected to significantly reduce production costs and improve environmental friendliness, making it an ideal goal for the polyolefin industry. The core bottleneck in achieving POE gas-phase polymerization lies in developing a suitable high-performance metallocene catalyst system.
[0005] Currently, directly applying metallocene catalysts traditionally used in solution polymerization to gas-phase polymerization faces serious problems such as rapid deactivation of catalyst active sites and unstable polymerization kinetics. The reasons include: First, at gas-phase polymerization operating temperatures (70~100℃), the local concentration of metallocene cationic active sites supported on the support surface is high, easily leading to irreversible bimolecular disproportionation or σ-bond metathesis reactions, resulting in deactivation; second, the polymerization reaction is carried out under solvent-free conditions, and the newly formed polymer physically embeds the active sites, blocking monomer diffusion pathways; third, residual silanol groups and other groups on the support surface continuously chemically poison the active sites. These multiple factors combined result in a "burst-rapid decay" characteristic in polymerization activity, failing to meet the requirements for long-term catalyst stability in continuous industrial production.
[0006] To address the aforementioned issues, existing solutions mainly include: high-temperature calcination of the support combined with organoaluminum pre-passivation treatment, construction of metallocene catalysts with restricted geometry (CGC), and the use of mesoporous molecular sieves as nano-confined supports. However, support pretreatment methods can only partially reduce poisoning, the passivation effect is not lasting and a reversible reaction can occur in the presence of MAO; CGC catalysts still lack sufficient thermal stability under gas-phase conditions, and their excessive sensitivity to hydrogen regulation limits the preparation of high molecular weight POE; mesoporous molecular sieves are too expensive, their synthesis is complex, and it is difficult to achieve stability breakthroughs through physical confinement alone. Summary of the Invention
[0007] The purpose of this invention is to overcome the above-mentioned shortcomings of the prior art and provide a metallocene catalyst, its preparation method, and its application. This catalyst, through a norbornene-bridged perfluoroalkyl composite structure, constructs a nano-reaction chamber within mesoporous channels that possesses triple functions of enhanced physical confinement, chemical shielding, and structural stability. This fundamentally blocks the bimolecular deactivation pathway of the active center and simultaneously inhibits structural collapse of the channels at high temperatures, significantly extending the lifespan of the metallocene catalyst in the high-temperature environment of gas-phase polymerization and achieving stable polymerization kinetics.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a metallocene catalyst comprising the following components by mass percentage: a nobornene / perfluoroalkyl dual-modified coarse-porous silica support: 50%–75%; methylaluminoxane: 20%–40%; and a zirconium compound: 1%–10%. The dual-modified support is prepared by pre-modification with nobornene triethoxysilane combined with an olefin cross-metathesis reaction with a perfluoroolefin.
[0009] Furthermore, the coarse-porous silica gel has an average pore size of 6-10 nm and a specific surface area of 280-400 m² before calcination. 2 / g, pore volume 0.8~1.5cm 3 / g, and is roasted at 400~600℃ for 4~12 hours before use.
[0010] Furthermore, the norbornene triethoxysilane is 5-(triethoxysilyl)-2-norbornene, and its addition amount is 3% to 10% of the mass of the coarse-pore silica gel.
[0011] Furthermore, the perfluoroolefin is perfluoro-1-decene or perfluoro-1-octene, and its addition amount is 5% to 20% of the mass of the NB-SiO2 support.
[0012] Furthermore, the Grubbs catalyst is a second-generation Grubbs catalyst, and its addition amount is 0.5% to 2.0% of the NB-SiO2 support mass.
[0013] Further, the zirconium compound is one of diphenylmethylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconia, or racemic-dimethylsilylbis(1-indenyl)zirconia.
[0014] Secondly, the present invention also provides a method for preparing the above-mentioned catalyst, comprising the following steps: (1) Norbornene modification: The calcined coarse-porous silica gel was dispersed in anhydrous toluene, and norbornenyltriethoxysilane (3%–10% of the mass of the coarse-porous silica gel) was added. The mixture was refluxed at 85±5℃ for 12–18 hours under an inert atmosphere. After the reaction was completed, the mixture was filtered, washed with toluene and n-hexane, and dried to obtain norbornenyl-modified silica gel support NB-SiO2.
[0015] (2) Olefin cross metathesis reaction: NB-SiO2 was dispersed in anhydrous dichloromethane, and a Grubbs second-generation catalyst (0.5%–2.0% by mass of NB-SiO2) and a perfluoroolefin (5%–20% by mass of NB-SiO2) were added. The reaction was carried out under nitrogen protection at 25±2℃ with stirring for 6–10 hours. Under the action of the Grubbs catalyst, the strained double bond on the norbornene ring underwent cross-metathesis with the perfluoroolefin, forming a C=C double-bonded perfluoroalkyl graft chain. After the reaction, the mixture was filtered, washed with dichloromethane and n-hexane, and dried to obtain the double-modified silica support F-NB-SiO2.
[0016] (3) MAO load: F-NB-SiO2 was dispersed in anhydrous toluene under an inert atmosphere, and a toluene solution of methylaluminoxane was added (the amount added was 10% to 30% of the mass of F-NB-SiO2 carrier based on aluminum element). The mixture was stirred at room temperature for 2 to 6 hours, filtered, washed, and dried to obtain MAO / F-NB-SiO2 composite carrier.
[0017] (4) Metallocene compound loading: The zirconium compound was dissolved in anhydrous toluene and slowly added to an anhydrous toluene suspension of MAO / F-NB-SiO2. The reaction was carried out at room temperature for 6 to 12 hours, and the mixture was filtered, washed, and dried under vacuum at 35°C to obtain the catalyst.
[0018] This invention utilizes a coupling condensation reaction between norbornene-based triethoxysilane and coarse-porous silica gel to anchor the silane onto the inner surface of the pores via Si-O-Si covalent bonds. Subsequently, perfluoroalkyl chains grafted via an olefin cross-metathesis reaction form a composite structure within the pores. The rigid norbornene-bridged structure of this composite structure more effectively separates the active centers into independent nanocavities, providing superior physical isolation compared to simple linear perfluoroalkyl modification. Furthermore, the rigid cyclic framework of the norbornene bridging structure effectively suppresses the thermally induced structural collapse of the mesoporous channels under the high temperature (70~95℃) conditions of gas-phase polymerization, maintaining the unobstructed flow of the channels and the full exposure of the active centers, resulting in a more stable channel structure. Meanwhile, the perfluoroalkyl chains form a dense superhydrophobic chemical shielding layer on the inner surface of the channels, effectively isolating the residual Si-OH in the deep layers of the carrier from poisoning the active centers. At the same time, the strong electron-withdrawing effect of fluorine atoms enhances the electrostatic binding force between the cationic active centers and MAO anions, resulting in stronger chemical shielding and electronic stability. This composite structure provides a highly uniform chemical microenvironment for the active centers, which is conducive to achieving stable polymerization kinetics and a uniform composition of the polymerization product.
[0019] Thirdly, the present invention provides the application of the above-mentioned metallocene POE catalyst in the gas-phase copolymerization of ethylene and α-olefin to prepare polyolefin elastomers, wherein the α-olefin is 1-butene, the polymerization method is gas-phase polymerization, the gas-phase polymerization temperature is 40~75℃, the polymerization pressure is 1.0~3.0MPa, and the molar ratio of hydrogen to ethylene is 0.0001~0.01.
[0020] Beneficial effects
[0021] Compared with the prior art, the present invention has the following significant advantages: (1) Significantly extended active lifespan: Under gas-phase polymerization conditions at 80℃, the active half-life of the catalyst of the present invention reaches 6 hours, which is 6 to 12 times longer than that of conventional MAO / silica gel supported catalysts (active half-life of about 30 to 60 minutes).
[0022] (2) Excellent high-temperature structural stability: The rigid network of norbornene bridging effectively inhibits the structural collapse of the channels at high temperatures, and the catalyst still maintains a high activity retention rate (>75%) under extreme conditions of 95℃.
[0023] (3) Excellent copolymerization ability is maintained: the 1-butene insertion rate can still reach 32~35 mol%, and the density range of the resulting POE product is 0.881~0.888 g / cm³. 3 . Attached Figure Description
[0024] Figure 1 This is a comparison chart of the activity-time curves of Example 1, Comparative Example 1, and the catalyst of Comparative Example 1 in gas-phase polymerization.
[0025] Figure 2 This is a flowchart illustrating the preparation process of the catalyst of this invention. Detailed Implementation
[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that the following embodiments are only for explaining the invention and not for limiting it. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0027] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.
[0028] Example 1
[0029] Metallocene POE catalysts for gas-phase polymerization processes are prepared via the following steps (e.g.) Figure 2 (as shown) Step 1: Pre-treatment of silica gel by calcination Weigh out 50g of coarse-pore silica microspheres SD-401 (average pore size 8.0nm, specific surface area 350m²). 2 / g, pore volume 1.2cm 3 / g) is placed in a quartz glass dish, with a thickness not exceeding 2cm. It is then placed in a programmable temperature controlled muffle furnace and heated to 150℃ at 2℃ / min under air atmosphere, and dried at this temperature for 4 hours; subsequently, the temperature is increased to 550℃ at 5℃ / min and calcined at this temperature for 8 hours. After naturally cooling to approximately 120℃, it is transferred to a preheated vacuum drying oven and dried at 120℃ and -0.095MPa for 2 hours. High-purity nitrogen is then introduced, and the oven is transferred to a glove box for cooling and later use.
[0030] Step 2: Norbornene modification Disperse 20.0 g of the calcined silica gel in 240 mL of anhydrous toluene and stir for 15 minutes to form a homogeneous suspension. Add 1.6 g (approximately 5.6 mmol) of 5-(triethoxysilyl)-2-norbornene (NB-TES) (8% of the silica gel mass). Connect to a Schlenk system and heat to 85 ± 2 °C under nitrogen protection, then reflux and stir for 16 hours.
[0031] After the reaction was completed, the mixture was cooled to approximately 40°C and filtered under reduced pressure under nitrogen protection. The filter cake was washed three times with 40 mL of anhydrous toluene, and then twice with 40 mL of anhydrous n-hexane. The mixture was then dried under vacuum at 50°C and -0.098 MPa for 8 hours to obtain 21.8 g of white powdered norbornene-modified silica gel support NB-SiO2.
[0032] Step 3: Olefin cross metathesis reaction 10.0 g of the NB-SiO2 prepared in step two was dispersed in 120 mL of anhydrous dichloromethane and stirred for 30 minutes. 0.12 g of Grubbs second-generation catalyst (1.2% of the NB-SiO2 mass) and 1.5 g of perfluoro-1-decene (15% of the NB-SiO2 mass) were added. The reaction was carried out under nitrogen protection at 25 ± 2 °C for 8 hours with stirring.
[0033] After the reaction was completed, the sample was filtered under reduced pressure under nitrogen protection, rinsed three times with 40 mL of anhydrous dichloromethane, and twice with 40 mL of anhydrous n-hexane. The sample was then dried under vacuum at 40 °C and -0.098 MPa for 6 hours to obtain 11.2 g of light yellow powdery double-modified silica support F-NB-SiO2 (fluorine content determined to be 4.2 ± 0.3 wt%, BJH average pore size decreased from 8.0 nm to 6.5 nm).
[0034] Step 4: MAO Load 5.0 g of the F-NB-SiO2 prepared in step 3 was dispersed in 65 mL of anhydrous toluene and stirred for 30 minutes. 15.0 g of MAO toluene solution (10 wt% Al content, containing approximately 1.5 g of Al) was added dropwise, and the mixture was stirred at room temperature for 4 hours. The mixture was filtered under nitrogen protection, washed twice with 30 mL of anhydrous toluene, and once with 30 mL of anhydrous n-hexane. It was then dried under vacuum at 40 °C and -0.098 MPa for 4 hours to obtain 7.2 g of white powder MAO / F-NB-SiO2 composite support.
[0035] Step 5: Loading with metallocene compounds 4.0 g of the MAO / F-NB-SiO2 prepared in step four was dispersed in 70 mL of anhydrous toluene. 0.25 g of diphenylmethylene (cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride (Zr-Cat) was dissolved in 25 mL of anhydrous toluene (with slight heating at 40 °C to aid dissolution), and the solution was slowly added dropwise over 30 minutes. The mixture was stirred at room temperature for 8 hours and then allowed to stand for 4 hours to age. The mixture was filtered under nitrogen protection, washed three times with 40 mL of anhydrous toluene until the filtrate was colorless, and then washed twice with 30 mL of anhydrous n-hexane. The solution was dried under vacuum at 35 °C and -0.098 MPa for 5 hours to obtain 4.8 g of orange-yellow free-flowing powder, which is the target catalyst Cat-Zr / F-NB-MAO / SiO2.
[0036] Final catalyst composition (mass percentage): F-NB-SiO2 65.5%, MAO2 8.6%, Zr-Cat 5.9%.
[0037] Example 2
[0038] The difference between this embodiment and Embodiment 1 is that perfluoro-1-octene is used instead of perfluoro-1-decene in step three, and the amount added is 1.2g (12% of the mass of NB-SiO2). The remaining steps and conditions are the same as in Embodiment 1.
[0039] The fluorine content of the obtained F-NB-SiO2 was 3.8 ± 0.3 wt%.
[0040] The final catalyst composition was 66.2% F-NB-SiO2, 8.2% MAO2, and 5.6% Zr-Cat.
[0041] Example 3
[0042] The difference between this embodiment and Example 1 is that in step five, the zirconium compound used is racemic-dimethylsilylbis(1-indyl)zirconia (rac-Me2Si(Ind)2ZrCl2), and the amount added is 0.2g. The remaining steps and conditions are the same as in Example 1.
[0043] The final catalyst composition was 68.0% F-NB-SiO2, 7.2% MAO2, and 4.8% Zr-Cat.
[0044] Comparative Example 1 10.0 g of calcined coarse-porous silica gel (same as in Example 1, calcined at 550°C for 8 hours) was dispersed in 120 mL of anhydrous toluene and stirred for 15 minutes to form a homogeneous suspension. 0.63 g (approximately 1.12 mmol) of heptadecafluorodecyltrimethoxysilane was added. The mixture was connected to a Schlenk system and heated to 85 ± 2°C under nitrogen protection, then refluxed and stirred for 16 hours. MAO loading and metallocene loading were then performed under the same procedures and conditions as in Example 1.
[0045] The final catalyst composition was 64.0% F-SiO2, 9.9% MAO2, and 6.1% Zr-Cat.
[0046] Comparative Example 2 Take 10.0 g of NB-SiO2 prepared in step two of Example 1, and directly perform MAO loading and metallocene loading without going through the metathesis reaction in step three (same as steps four and five of Example 1).
[0047] The final catalyst composition was 66.8% NB-SiO2, 7.8% MAO2, and 5.4% Zr-Cat.
[0048] The catalysts prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were used to evaluate the copolymerization of ethylene / 1-butene in a 2L horizontal stirred bed gas-phase polymerization reactor.
[0049] Polymerization conditions: reaction temperature 65±1℃, total pressure 2.0MPa, ethylene partial pressure 1.0MPa, hydrogen / ethylene molar ratio 0.002, 1-butene / ethylene molar ratio 0.25 (introduced into the reactor via nitrogen through a 1-butene saturator), catalyst addition of approximately 100mg, triisobutylaluminum (TIBA) pre-added as an impurity scavenger (Al content approximately 1mmol), polymerization time 6 hours.
[0050] Polymer activity was monitored by sampling at regular intervals during polymerization. After polymerization, polymer particles were discharged, the reaction was terminated by acidification with methanol, and the particles were washed, vacuum dried at 60°C to constant weight, and then weighed. Polymer density was determined using the density gradient column method (ASTM D1505), 1-butene insertion rate was determined using infrared spectroscopy (ASTM D5576), and molecular weight and molecular weight distribution were determined using high-temperature GPC. The results are shown in Table 1. Table 1 Evaluation results of gas-phase polymerization for each example and comparative example.
[0051] Results analysis: (1) Activity and stability: The total activity of Example 1 reached 1.05 kg / gcat·h after 6 hours, which is 176% higher than that of Comparative Example 1. The active half-life is over 6 hours, which is much better than the 3.2 hours of Comparative Example 1 and the 1.5 hours of Comparative Example 2. The activity retention rate at 80°C for 6 hours reached 78%, and the catalyst maintained excellent stability during long-term polymerization.
[0052] (2) High-temperature structural stability: At an extreme temperature of 95°C, the activity retention rate of Example 1 still reached 76%, while that of Comparative Example 1 dropped sharply to 35%, and that of Comparative Example 2 was only 25%. The catalyst of the present invention has high-temperature structural stability.
[0053] (3) Copolymerization performance: The 1-butene insertion rate of Example 1 reached 35.0 mol%, which was higher than that of Comparative Example 1 (27.0 mol%) and Comparative Example 2 (24.0 mol%), and the polymer density was between 0.881 and 0.888 g / cm³. 3 The ideal PoE range.
[0054] (4) Molecular weight distribution: The molecular weight distribution of the product in the example (Mw / Mn=2.4~3.0) was significantly narrower than that of the comparative example (4.0~4.5), indicating that its composite structure provides a more uniform microenvironment for the active center.
[0055] Figure 1 This is a comparison of the activity-time curves of the catalyst in Example 1 of the present invention with those of Comparative Examples 1 and 2 in gas-phase polymerization at 65°C. The solid line represents Example 1, the dotted line represents Comparative Example 1, and the dashed line represents Comparative Example 2. Figure 1 It can be seen intuitively from the middle, The catalyst in Example 1 showed no explosive exothermic peak and its activity declined in a near-linear and gradual manner, with an activity retention rate of 78% after 6 hours. The catalyst in Comparative Example 1 exhibited typical "explosive-rapid decay" kinetic characteristics, while the catalyst in Comparative Example 2 was rapidly deactivated after the initial explosive reaction and almost completely deactivated after 6 hours.
[0056] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A metallocene catalyst, characterized in that, The catalyst comprises the following components by mass percentage: norbornene / perfluoroalkyl dual-modified coarse-porous silica support: 50%~75%; methylaluminoxane: 20%~40%; zirconium oxychloride: 1%~10%. The norbornene-alkenyl / perfluoroalkyl dual-modified coarse-porous silica support was prepared by the following two-step method: (a) calcined coarse-porous silica was coupled with norbornene-alkenyltriethoxysilane to obtain norbornene-alkenyl-modified silica support NB-SiO2; (b) in the presence of Grubbs catalyst, NB-SiO2 was subjected to olefin cross-metathesis reaction with perfluoroolefin to obtain dual-modified silica support F-NB-SiO2.
2. The metallocene catalyst according to claim 1, characterized in that, The coarse-porous silica gel has an average pore size of 6-10 nm and a specific surface area of 280-400 nm before calcination. 2 / g, pore volume 0.8~1.5cm 3 / g.
3. The metallocene catalyst according to claim 2, characterized in that, The coarse-porous silica gel is calcined at a temperature of 400~600℃ for 4~12 hours.
4. The metallocene catalyst according to claim 1, characterized in that, The norbornene-based triethoxysilane has the structural formula 5-(triethoxysilyl)-2-norbornene, and its addition amount is 3% to 10% of the mass of the coarse-pore silica gel.
5. The metallocene catalyst according to claim 1, characterized in that, The perfluoroolefin is one of perfluoro-1-decene or perfluoro-1-octene, and its addition amount is 5% to 20% of the mass of the NB-SiO2 carrier.
6. The metallocene catalyst according to claim 1, characterized in that, The Grubbs catalyst is one of the second-generation Grubbs catalyst (bis(tricyclohexylphosphine)benzyl ruthenium dichloride) or Hoveyda-Grubbs second-generation catalyst, and its addition amount is 0.5% to 2.0% of the NB-SiO2 support mass.
7. The metallocene catalyst according to claim 1, characterized in that, The zirconium compound is one of diphenylmethylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconia, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconia, or racemic-dimethylsilylbis(1-indenyl)zirconia.
8. A method for preparing a metallocene catalyst as described in any one of claims 1 to 7, characterized in that... Includes the following steps: (1) The coarse-porous silica gel after calcination was dispersed in anhydrous toluene, and norbornen-alkenyltriethoxysilane was added. The mixture was refluxed at 85±5℃ for 12~18 hours under an inert atmosphere. After filtration, washing and drying, the norbornen-alkenyl modified silica gel carrier NB-SiO2 was obtained. (2) NB-SiO2 was dispersed in anhydrous dichloromethane, and Grubbs second-generation catalyst and perfluoroolefin were added. The mixture was stirred at 25±2℃ for 6~10 hours under nitrogen protection. After filtration, washing and drying, double-modified silica support F-NB-SiO2 was obtained. (3) F-NB-SiO2 was dispersed in anhydrous toluene under an inert atmosphere, and a toluene solution of methylaluminoxane was added. The mixture was stirred at room temperature for 2 to 6 hours, filtered, washed, and dried to obtain the MAO / F-NB-SiO2 composite support. The amount of methylaluminoxane added was 10% to 30% of the mass of the F-NB-SiO2 support, calculated based on aluminum element. (4) Dissolve the zirconium compound in anhydrous toluene, slowly add it to an anhydrous toluene suspension of MAO / F-NB-SiO2, react at room temperature for 6 to 12 hours, filter, wash and vacuum dry to obtain the catalyst.
9. The use of a metallocene catalyst as described in any one of claims 1 to 7 in the gas-phase copolymerization of ethylene and α-olefins to prepare polyolefin elastomers, characterized in that, The α-olefin is 1-butene.
10. The application of the metallocene catalyst according to claim 9, characterized in that, The gas-phase polymerization temperature is 40~75℃, the polymerization pressure is 1.0~3.0MPa, and the molar ratio of hydrogen to ethylene is 0.0001~0.01.